Risk based hybrid security model for enhancing eHealth services of cloud system - Ullah, Azmat; Hasan, Md. Tasnimul; Hossain, Imam; Das, Tonmoy (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.